CATATAN KECIL MENGENAI DESAIN RISET DESKRIPTIF KUALITATIF - Suardi, Wahdi (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2020)
Qualitative description (QD) is a label used in qualitative research for studies that are descriptive in nature and widely used to describe of social-related phenomena. The philosophy of QD is pragmatic approach, overtones of other qualitative approach and probably the least theoretical of the qualitative approaches. This variability may indicate that there are no clear boundaries between QD and other strategies. QD has been identified as important and appropriate for research questions focused on discovering the who, what, and where of event or experiences and on gaining insight from a poorly understood phenomenon. QD should be the method of choice only when a description of a phenomenon is desired. Purposeful and maximum variation sampling may be used in QD studies. Data collection techniques usually include minimally-to-moderately structured open-ended interviews with individuals or focus groups. Qualitative content analysis using modifiable coding systems is analysis strategy of choice in QD studies. QD studies result in a rich, straight description of experience, perception, or event using language from the collected data through lon-inference interpretation during data analysis.